Biobased Materials for Agricultural Applications - Katherine Gatzos; Alejandro G. Marangoni; Erica Pensini (International Journal of Agricultural Sciences, 2021)
Zein-based biomaterials were used as alternatives to plastic to produce spray-on mulching films and horticulture pots. Spray-on zein-based mulching films were prepared using basic zein solutions in water solidified with either potassium salts or acetic acid. In the lab, zein mulching films decreased moisture loss by approximately 10% over a 16 days period, reduced phosphorus runoff by 70%, and prevented soil erosion upon exposure to simulated rainfall events. Healthy growth of cherry radishes and pickling cucumbers was observed with zein mulch solidified with potassium phosphate and glacial acetic acid, indicating that zein mulch is a promising alternative to plastic mulching films. Moreover, zein was used to produce horticulture pots in combination with either linseed or tung oil. Zein pots did not degrade upon exposure to either -18℃ for seven days or outdoor sun for seven days or when they were submerged in aqueous solutions at pH 4, 6, and 9. Food grade dyes were incorporated into the potting material to enhance visual appeal without affecting the integrity of the zein material. Heirloom radish seeds germinated in zein pots were taller compared to those grown in commercial peat pots, indicating that zein pots can be successfully used